PENERAPAN TEORI BELAJAR BEHAVIORISME DALAM PEMBELAJARAN (STUDI PADA ANAK) - A. Mustika Abidin (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2022)
This article discusses the application of behaviorism learning theory in learning (studies in children) through the literature review method. In behaviorism learning theory has a basic concept that learning is an interaction between stimulus (stimulus) and response (response). This theory prioritizes measurement, because measurement is an important thing to see whether or not there is a change in behavior in children. The application of this theory requires teachers to identify learning objectives, conduct learning analysis, identify early characteristics and abilities of children, determine indicators of learning success, develop teaching materials, develop learning strategies to be used, observe stimuli that might be given to children such as exercises or assignments, observing and analyzing student responses, providing reinforcement, both positive and negative reinforcement, and finally revising learning activitiesArtikel ini membahas mengenai penerapan teori belajar behaviorisme dalam pembelajaran (studi pada anak) melalui metode tinjauan literatur. Dalam teori belajar behaviorisme memiliki konsep dasar bahwa belajar merupakan interaksi antara rangsangan (stimulus) dan tanggapan (respon). Teori ini mengutamakan pengukuran, sebab pengukuran merupakan suatu hal penting untuk melihat terjadi tidaknya perubahan tingkah laku pada anak. Penerapan teori ini menuntut guru agar mengindentifikasi tujuan pembelajaran, melakukan analisis pembelajaran, mengidentifikasi karakteristik dan kemampuan awal anak, menentukan indikator keberhasilan belajar, mengembangkan bahan ajar, mengembangkan strategi pembelajaran yang akan digunakan, mengamati stimulus yang mungkin bisa diberikan kepada anak seperti latihan atau tugas, mengamati dan menganalisis respon pembelajar, memberikan penguatan (reinforcement) baik penguatan positif maupun negatif, dan terakhir merevisi kegiatan pembelajaran.